Automatic migration from synchronous to asynchronous JavaScript APIs - Gokhale, Satyajit; Turcotte, Alexi; Tip, Frank (Proceedings of ACM on programming languages, 2021)
The JavaScript ecosystem provides equivalent synchronous and asynchronous Application Programming Interfaces (APIs) for many commonly used I/O operations. Synchronous APIs involve straightforward sequential control flow that makes them easy to use and understand, but their "blocking" behavior may result in poor responsiveness or performance. Asynchronous APIs impose a higher syntactic burden that relies on callbacks, promises, and higher-order functions. On the other hand, their nonblocking behavior enables applications to scale better and remain responsive while I/O requests are being processed. While it is generally understood that asynchronous APIs have better performance characteristics, many applications still rely on synchronous APIs. In this paper, we present a refactoring technique for assisting programmers with the migration from synchronous to asynchronous APIs. The technique relies on static analysis to determine where calls to synchronous API functions can be replaced with their asynchronous counterparts, relying on JavaScript's async/await feature to minimize disruption to the source code. Since the static analysis is potentially unsound, the proposed refactorings are presented as suggestions that must be reviewed and confirmed by the programmer. The technique was implemented in a tool named Desynchronizer. In an empirical evaluation on 12 subject applications containing 316 synchronous API calls, Desynchronizer identified 256 of these as candidates for refactoring. Of these candidates, 244 were transformed successfully, and only 12 resulted in behavioral changes. Further inspection of these cases revealed that the majority of these issues can be attributed to unsoundness in the call graph.